U-Pb zircon ages and Hf isotopic compositions of metasedimentary rocks from the Grove Subglacial Highlands, East Antarctica: Constraints on the provenance of protoliths and timing of sedimentation and metamorphism - Wang, Wei; Liu, Xiaochun; Zhao, Yue; Zheng, Guanggao; Chen, Longyao (Precambrian Research, 2016)
To explore the geological evolution of the Grove Subglacial Highlands and their relationship with other terranes in the Prince Charles Mountains-Prydz Bay region of East Antarctica, 10 samples of metasedimentary rock were collected from glacial moraines in the Grove Mountains for zircon U-Pb dating and Hf isotopic analysis. Detrital zircon grains from all rocks have oscillatory zoned magmatic cores and diffusely zoned metamorphic rims. U-Pb ages from the cores are mainly concentrated in six populations: 3.4-3.2, 2.8, 2.6-2.3, 2.2-1.8, 1.8-1.5 and 1.5-0.95 Ga. Their initial stif values are -4.1 to +5.5, -12.5 to +4.9, -12.6 to +3.3, -13.0 to +4.7, -14.2 to +11.0, and -20.5 to +10.0, and their corresponding Hf model ages are 3.7-3.2, 3.4-3.1, 3.2-2.6, 2.9-2.1, 2.7-1.7, and 2.4-1.2 Ga, respectively. The maximum depositional ages of ca. 1090-940 Ma were calculated from the youngest detrital zircon cores of each sample. All age populations and Hf isotopic compositions can be found their provenances in the Prince Charles Mountains-Prydz Bay-Eastern Ghats region, indicating a genetic relationship between the two regions. However, we cannot rule out the possibility that the precursor materials of metasedimentary rocks from the Grove Subglacial Highlands were derived from the southern interior of the East Antarctic Shield (e.g., the Gamburtsev Subglacial Mountains and Vostok Subglacial Highlands). The late Mesoproterozoic/early Neoproterozoic (ca. 990-900 Ma) metamorphic event was not identified in our detrital zircon grains, and all metamorphic zircon rims were dated at ca. 560-540 Ma. This suggests that the collision suture of the late Neoproterozoic/Cambrian Prydz Belt should lie to the south of the Grove Subglacial Highlands. (C) 2016 Elsevier B.V. All rights reserved. Chinese Polar Environment Comprehensive Investigation & Assessment Programmes [CHINARE2015-02-05]; National Natural Science Foundation of China [41530209]; Geological Investigation Project of the China Geological Survey [12120113019000] SCI(E) ARTICLE liuxchqw@cags.ac.cn 135-150 275